Identifying the Relevant Local Population for Environmental Impact Assessments of Mobile Marine Fauna - Chabanne, Delphine B. H.; Finn, Hugh; Bejder, Lars (Frontiers in Marine Science, 2017)
Environmental impact assessments must be addressed at an appropriate scale of biological organization for the species affected. It can be challenging to identify the relevant local wildlife population for impact assessment for those species that are continuously distributed and highly mobile. Here, we document the existence of local communities of Indo-Pacific bottlenose dolphins (Tursiops aduncus) inhabiting coastal and estuarine waters of Perth, Western Australia, where major coastal developments have been undertaken or are proposed. Using sighting histories from a four-year photo-identification study, we investigated fine-scale, social community structure of dolphins based on measures of social affinity and network (Half-Weight Index - HWI, preferred dyadic association tests, and Lagged Association Rates - LAR), home ranges, residency patterns (Lagged Identification Rates - LIR), and genetic relatedness. Analyses revealed four socially and spatially distinct, mixed-sex communities. The four communities had distinctive social patterns varying in strength, site fidelity and residency patterns. Overlap in home ranges and relatedness explained little to none of the association patterns between individuals, suggesting complex local social structures. The study demonstrated that environmental impact assessments for mobile, continuously distributed must evaluate impacts in light of local population structure, especially where proposed developments may affect core habitats of resident communities or sub-populations. Here, the risk of local extinction is particularly significant for an estuarine community because of its small size, limited connectivity with adjacent communities, and use of areas subject to intensive human use. In the absence of information about fine-scale population structure, impact assessments may fail to consider the appropriate biological context.